Association of Helicobacter pylori Infection With Carotid Atherosclerosis in a Northern Chinese Population: A Cross-Sectional Study - Zhang, Pu; He, Qian; Song, Daiyu; Wang, Yiying; Liu, Xinyue; Ding, Guoyong; Xing, Weijia (Frontiers in Cardiovascular Medicine, 2022)
Numerous studies have shown that Helicobacter pylori (HP) infection may be involved in the development of carotid atherosclerosis (CAS), but this conclusion is still controversial. The purpose of this study was to explore whether there is a positive association between HP infection and CAS occurrence. We collected data on demographic characteristics, lifestyle, and disease history of the participants by questionnaire. We obtained clinical anthropometric data and blood samples of the participants from clinical examinations and laboratory work. The 13C urea breath test (13C-UBT) was performed to assess the HP infection status, and carotid ultrasonography was used to diagnose the CAS and plaque types. Univariate analysis and multivariate logistic regression were used to identify the relationship between HP infection and CAS. A total of 1,424 participants were recruited for this study. A total of 740 HP-positive individuals and 684 HP-negative individuals were identified, and 345 participants were diagnosed with CAS. The prevalence of CAS was higher in the HP-positive group (26.4%) than in the HP-negative group (21.7%) (P<0.05). A significantly higher prevalence of carotid intima-media thickening, carotid plaque, and carotid stenosis was identified in the HP-positive group than in the HP-negative group (P<0.05). There was no significant difference in the detection rate of unstable plaques between the HP-positive and HP-negative groups (P>0.05). In multivariate models adjusted for covariates, HP infection showed a positive association with CAS, independent of other risk factors (OR range: 1.283-1.333, P<0.05). HP infection independently accounted for approximately 5% of the CAS risk. A positive association between HP infection and CAS was demonstrated in this study. HP infection might be an independent risk factor for CAS. Although the effect of HP infection on CAS observed in our study was less than that of traditional risk factors, we believe that this is an indispensable advance in the etiological study of CAS. These results imply that the microbial population might play an essential role in CAS, which provides a new perspective for the primary prevention of CAS.